Knowledge, Attitude, and Practice of Nursing Home Staff Regarding Physical Restraint in China: A Cross-Sectional Multicenter Study - Yaqin Li; YaWen Wang; Yechun Gu; Daqiang Gong; Sisi Jiang; Jufang Li; Hongbo Xu (Frontiers Media S.A., 2022)
BackgroundRestraint is widely used in nursing homes to address safety concerns. However, many studies have shown that improper restraint can lead to many adverse outcomes. Nursing staff are the main practitioners of physical restraint in nursing homes and play an important role in restraint decision-making and management. In China, there is still a lack of large-scale surveys on the current situation regarding the use of restraint. This study aimed to identify this situation and the influencing factors of the knowledge, attitude, and practice of nursing staff regarding physical restraint in elderly care institutions.MethodsA cross-sectional multicenter descriptive study was conducted. A total of 311 staff in 25 elderly care institutions in Zhejiang Province were recruited using a quota sampling method. A homemade questionnaire was administered to collect general information and information on knowledge, attitude and practice regarding physical restraint.ResultsThe average scoring rates of the knowledge and attitude dimensions of the 311 staff were 48.7 and 75.6%, respectively. The average scoring rate of the practice dimension of 140 staff who implemented restraint was 80.1%. Educational background and training experience were the influencing factors of restraint knowledge. Training experience, educational background and professional title were the influencing factors of restraint attitude. Restraint knowledge and length of service were the influencing factors of restraint practice.ConclusionsKnowledge of physical restraint among nursing staff is not promising. Their attitude toward restraint was inappropriate or irresponsible in some aspects. Restraint practice is not sufficiently standardized. It is necessary to strengthen restraint training for nursing staff to improve their overall level of restraint knowledge, attitude and practice.